Study the Impact on Government Policies of Niti Aayog: An Analysis of the Impact of NITI Aayog on Government Policies and Governance in India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
On 1 January 2015, India‟s 64-year-old apex policy-making body, the Planning Commission,was replaced by a new institution, the National Institution for Transforming India (NITI) Aayog. While it isstill too early to assess the NITI Aayog‟s impact on India‟s complex policy landscape, or the full extent ofits social and political implications, the emerging architecture of the new institution provides valuableinsights into the Modi government‟s economic policy priorities and preferred style of governance. One ofthe main objectives of NITI Aayog is, „To study NITI Aayog will spur innovative thinking by objective„experts‟ and promote „co-operative federalism‟ by enhancing the voice and influence of the states, thenew institution is being crafted to enlarge the power of the executive government and the prime minister.